(untitled) (Jurnal Biota, 2017)
DHF (Dengue) disease is transmitted through mosquito vectorAedes aegypti.One way to do control the Dengue vector is to use insecticide made from natural materials and is environmentally friendly with lemon peel extract (Citrusaurantifolia). This study aims to determine the effectiveness of extracts of lemon peel (Citrus aurantifolia) in killing the third instar larvae Aedesaegypti with various concentrations and time variations. This were an experimental laboratory researchs using various concentrations of extract limes peel (Citrusaurantifolia) 1%, 2%, 3%, 4%, 5%, 6%, and 7% in which there 25 larvae Aedes aegypti and using a variation of 30, 60, 90, 120, 180, 240, 300, and 1440 minutes after contact with the extracts limes peel (Citrusaurantifolia). Effective concentration to kill larvae of Aedes aegypti by 50% (IC50) was the concentration of 3.419%.